Sunk in love - McBreen, Heather (Berkley Romance, 2026)
"A second chance at love sets sail when a couple on the verge of divorce pretend they're still together for one last family trip, from the author of Wedding Dashers. Roslyn and Liam met nine years ago and have been the perfect couple ever since. Through every up and down, every milestone-from Liam's residency to the publication of Roslyn's debut romance-they've been each other's rocks. Until now. Pulled apart by the untimely death of Roslyn's mom and the undertow of grief, they're now navigating the final wave in their marriage: divorce. Heartbroken and unsure how to tell her family she's called it quits with everyone's favorite son-in-law, Roslyn keeps the impending divorce a secret. But when Roslyn's grandparents ask if Liam can officiate their vow renewal ceremony aboard a Hawaiian cruise during their annual vacation, Roslyn needs to tell the truth or figure out a way to keep her secret. A week trapped at sea with her ex isn't ideal, but neither Roslyn nor Liam want to rock the boat, so they concoct a plan-they'll fake it. After five years of marriage, they can figure out how to pretend for jungle hikes and mai tais, right? But when reality and make-believe start to blur, and old feelings begin to resurface, Roslyn and Liam have to decide whether it's sink or swim for their marriage"-- Provided by publisher.